Operational Risk Assessment for International Transport Corridor: A Case Study of China-Pakistan Economic Corridor - Yang Lei; Chengfeng Huang; Yuan Wu (Discrete Dynamics in Nature and Society)
The international transport corridor is the basis and carrier of economic and trade exchanges between countries and regions. International transport corridors span different countries and regions, coupled with the long distance, complicated transportation environment and process, which determines the potential risks of the operation of the transport corridors. Therefore, accurately identifying and assessing the risk of international channels are an important prerequisite for ensuring its safe and stable operation. The expert scoring method is used to collect the basic data of risk identification, and the hesitant fuzzy decision theory is introduced. The dependent linguistic ordered weighted geometric (DLOWG) operator and the Failure Mode and Effect Analysis (FMEA) method are used in combination. Taking the China-Pakistan Economic Corridor (CPEC) as an example, evaluate the operational risks of the international transport corridor. The research results show that corruption, terrorism, and policy stability are the top three risk factors in the operation of the China-Pakistan transport corridor. The risk management and control should focus on these three types of risks and strengthen the security management along the route. Strengthen policy docking and communication, maintain political stability, and strengthen antiterrorism cooperation.